THE USE OF WILDLING OF TISUK (Hybiscus macrophyllus) FOR ENRICHMENT PLANTING OF PRIVATE FOREST AT TASIKMALAYA - Aris Sudomo; Encep Rachman (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
Research on tisuk (Hibiscus macrophyllus) wildlings was conducted in the private forest area in Pasirbatang Village, Manonjaya Sub-District, Tasikmalaya District. The material of tisuk wildings was grown in nursery area of Ciamis Forestry Research Institute. The research was conducted on September 2007, starting with the private forest observation, which covers the potency of natural seedling spreading and the measurement of 2 years old-tisuk wildling, which came from natural seedling. The diameter growth of 2 years old-tisuk natural seedling that belong to the private forest farmer are 5.6 cm, 4.9 cm and 7.1 cm, while its height are 6.0 cm, 6.3 cm and 7.1 cm. The huge number of tisuk wildling availability under the tisuk stand has high potency to be the material for forest regeneration. Some of its techniques are covering the big tree selection, tisuk natural seedling selection, taking off, packaging, tisuk natural leaf cutting, replacement and seedling maintaining.